"A bend in time": Shaping the sheath facilitates left atrial appendage closure. Issue 5 (23rd May 2015) - Gafoor, Sameer; Heuer, Luisa; Schulz, Philipp; Matic, Predrag; Franke, Jennifer; Bertog, Stefan; Reinartz, Markus; Vaskelyte, Laura; Hofmann, Ilona; Sievert, Horst
<x xml:space="preserve">Abstract</x> Objectives The purpose of this study is to determine feasibility, safety, and effectiveness of the "shape‐the‐sheath" method in left atrial appendage closure. Background LAA occlusion is often a difficult procedure, due to not just the learning curve but also the three‐dimensional variable nature of the left atrial appendage. Multiple sheaths have been created for various takeoffs. The purpose of this article is to show the feasibility of the "shape‐the‐sheath" method in left atrial appendage closure. Methods Ten consecutive patients undergoing LAA occlusion without the "shape‐the‐sheath" method were compared to 10 consecutive patients undergoing LAA occlusion with the "shape‐the‐sheath" method using the Amplatzer Cardiac Plug (ACP) system and the Amplatzer TorqVue 45 × 45 sheath. Results The "shape‐the‐sheath" method resulted in significant decreases in fluoroscopy time (7.2 ± 3.0 min vs. 13.7 ± 6.7 min, P < 0.05), number of partial recaptures (0% vs. 50%, P < 0.05), with a trend toward decrease in the number of complete recaptures (0 vs. 40%, P = 0.09) compared to conventional sheath use. Conclusions Shaping‐the‐sheath is a simple, elegant way to help conform delivery systems to better access the LAA and ensure stable position. Further experience with this procedure optimization step is warranted. © 2015 Wiley Periodicals, Inc.